Breast Milk: A Meal Worth Having - Duale, Anoud; Singh, Parul; Al Khodor, Souhaila (Frontiers in Nutrition, 2022)
A mother is gifted with breast milk, the natural source of nutrition for her infant. In addition to the wealth of macro and micro-nutrients, human milk also contains many microorganisms, few of which originate from the mother, while others are acquired from the mouth of the infant and the surroundings. Among these microbes, the most commonly residing bacteria are Staphylococci, Streptococci, Lactobacilli and Bifidobacteria. These microorganisms initiate and help the development of the milk microbiota as well as the microbiota of the gastrointestinal tract in infants, and contribute to developing immune regulatory factors such as cytokines, growth factors, lactoferrin among others. These factors play an important role in reducing the risk of developing chronic diseases like type 2 diabetes, asthma and others later in life. In this review, we will summarize the known benefits of breastfeeding and highlight the role of the breast milk microbiota and its cross-talk with the immune system in breastfed babies during the early years of life.